Science and innovation dynamics and policy in Scotland: The perceived impact of enhanced autonomy. (1st March 2017) - Mastroeni, Michele; Omidvar, Omid; Rosiello, Alessandro; Tait, Joyce; Wield, David
The Scottish referendum of 2014 encouraged massive public debate, including on Scotland's scientific performance and ability to harness innovation and increase global competitiveness. The science base in Scotland has traditionally been strong but has not translated well into innovation. This article uses statistical data, over 30 interviews and two workshops with business and policy leaders, to analyse key scientific and industrial innovation dynamics, using a regional innovation systems (RIS) approach. It investigates the perceived impact of increased autonomy on the dynamics of the Scottish innovation system (SIS). The article shows the weak relationship between science and innovation, and evidences the static nature of Scottish innovation policy geared to bridging a gap rather than improving the dynamics of the various elements in the innovation system. It suggests that an approach which aims to spur evolution in specific elements of the territorial governance system would strengthen Scottish innovation capabilities.